Haemodynamic changes in pulmonary hypertension in patients with interstitial lung disease treated with PDE‐5 inhibitors. Issue 5 (3rd April 2014) - Zimmermann, Gregor S.; von Wulffen, Werner; Huppmann, Patrick; Meis, Tobias; Ihle, Franziska; Geiseler, Jens; Leuchte, Hanno H.; Tufman, Amanda; Behr, Juergen; Neurohr, Claus
Abstract Background and objective Interstitial lung diseases (ILD) are often associated with pulmonary hypertension (PH). This study aimed to evaluate the therapeutic benefit of phosphodiesterase‐5 (PDE‐5) inhibitors in pulmonary hypertension secondary to ILD. Methods Patients with ILD and PH were treated with sildenafil or tadalafil. Right heart catheterization was performed before and after a minimum of 3‐month treatment. In addition, lung function, 6‐min walk distance (6MWD) and plasma brain natriuretic peptide (BNP) concentration were assessed. Results Ten ILD patients (three female, mean age 64.4 ± 9.0 years, six with idiopathic pulmonary fibrosis (IPF), four with hypersensitivity pneumonitis, (HP)) with significant precapillary PH (mean pulmonary artery pressure (PAPm) ≥ 25 mmHg, pulmonary vascular resistance (PVR) > 280 dyn*s*cm−5; pulmonary artery wedge pressure (PAWPm) ≤ 15 mmHg) were treated with either sildenafil (n = 5) or tadalafil (n = 5). Pulmonary haemodynamics were severely impaired at baseline (PAPm 42.9 ± 5.4 mmHg; cardiac index (CI) 2.7 ± 0.6 L/min/m2; PVR 519 ± 131 dyn × sec × cm−5). After mean follow‐up of 6.9 ± 5.8 months an increase in CI (2.9 ± 0.7 L/min/m2, P = 0.04) and a decrease in PVR (403 ± 190 dyn × sec × cm−5, P = 0.03) were observed. 6MWD and BNP did not change significantly. Conclusions Our data suggest that treatment with PDE‐5 inhibitors improves pulmonary haemodynamic patients with PH secondary to ILD.